Thrombosis after liver transplantation for hepatocellular carcinoma. - Ida Martinelli; Francesca R Ponziani; Alberto Maino; Sherrie Bhoori; Maria Abbattista; Umberto Maggi; Tullia M De Feo; Paolo Bucciarelli; Andrea Artoni; Elena Longhi; Marta Serafini; Giorgio Rossi; et al. (PLoS ONE, 2017)
The influence of thrombosis on the prognosis of patients with hepatocellular carcinoma (HCC) after liver transplantation (LT) and the role of the commonest inherited thrombophilia abnormalities factor V Leiden and prothrombin G20210A in the development of thrombosis are unknown. We investigated a cohort of patients who underwent LT for HCC with the aim to estimate the incidence rate (IR) of thrombosis, its influence on mortality and re-transplantation rates and, in the frame of a nested case-control study, the role of thrombophilia in donors and recipients for the development of thrombosis. Four-hundred and thirty patients underwent LT and were followed for a median of 7.2 years. Twenty-six recipients (6%) developed thrombosis (IR 1.06 [95%CI: 0.71-1.53] per 100 pts-yr). Mortality rate after LT was 3.95 (95%CI: 3.22-4.79) per 100 pts-yr and was not influenced by thrombosis. Re-transplantation was planned for 33 patients and was more common in patients with thrombosis than in those without (HR 2.50 [95%CI: 0.87-7.17]). The risk of thrombosis was 4 times higher in recipients with thrombophilia than in those without (OR 4.23 [95%CI: 0.99-18.04]) and 6 times higher when the analysis was restricted to venous thrombosis (OR 6.26 [95%CI: 1.19-32.85]). The presence of inherited thrombophilia in the donors did not increase the risk of thrombosis of the recipient. In conclusion, thrombosis is a complication of 6% of patients transplanted for HCC and increases the risk of re-transplantation but not of mortality. The risk of thrombosis, particularly venous, is increased in the presence of thrombophilia abnormalities in the recipients.